The Manifestation Of Cultural Peculiarities From The Point Of View Of Cultural Shock In The Translation Of Literary Works (Texas Journal of Philology, Culture and History, 2024)
This theme explores the intricate relationship between language, culture, and translation in the context of literary works. It delves into how translators navigate and convey cultural nuances, peculiarities, and idiosyncrasies embedded within original texts to target audiences. Cultural peculiarities encompass a wide array of elements including customs, traditions, social norms, beliefs, and historical references specific to a particular culture. The process of translating literary works involves not only linguistic accuracy but also the ability to preserve and transmit these cultural nuances effectively. This annotation will examine various approaches and challenges faced by translators in faithfully rendering cultural elements while maintaining the integrity and readability of the translated text. It aims to highlight the importance of cultural sensitivity and adaptation in ensuring that the essence of the original work is preserved and resonates with diverse readerships across different cultural contexts